ANALISIS VISUAL PADA SAMPUL DEPAN MAJALAH DESAIN GRAFIS “CONCEPT” EDISI ULTAH PERDANA (Sebuah Kajian Semiotika) - Prayanto WH (DeKaVe, 2011)
Magazine is one of the forms of mass media that has fungsikomunikasi to convey information to mass audiences. The cover is an important element because it is through cover / cover one can guess the contents of the magazine, as well as further interested to know further information contained therein. On a magazine cover consists of drawings and writings are arranged in such a way that looks interesting and has meaning Press publications, especially magazines, today's not enough just to rely on the quality of news or manuscript, although verbal aspect is very important. It must be recognized that the visual aspects (design) as the cover / envelope has crucial role to capture the prospective reader. For the cover of a magazine is a window that shows the content information, can be either a text or photographs, illustrations, and design elements. The function of a magazine cover is to attract, dazzle prospective readers, by way influence the thoughts flow in a short time. So it's no wonder much current the magazine publisher who made the cover of such a way as to attract the attention of prospective readers. Thus the task of designers to magazine cover to create designs that attract the attention of the reader becomes increasingly severe. This study tries to analyze a visual on the front cover Magazine Graphic Design 'Concept' birthday inaugural edition by using the Roland Barthes' semiotic approach. As Roland Barthes (1984), any simple "design work (magazine cover)" continue to play in management of the sign. So that will generate a message (image) specific. Design cover, usually contains the elements of the sign in the form of objects, context of the environment, people or other beings who provide meaning to objects, and text (of writing) that reinforce the meaning.Keyword: cover, magazine Concept, semiotics